Analisis Perbandingan Resiko dan Pengembalian Hasil Investasi pada Perbankan Syariah dan Konvensional Aplikasi Metode Value at Risk (VaR) dan Risk Adjusted Return Of Capital (RAROC) di BRI Syari’ah dan BRI - Muhamad Annas; Muhammad Alaika Nasrulloh; Sumari Mawardi (Jurnal Istiqro, 2020)
The purpose of this study is to study investment income that has been adjusted to the risk of deposits, mudharabah, which have Islamic bank and conventional bank obligations, to determine the level of ability of Islamic and conventional banks in the use of risk that can erode capital. This research uses empirical inquiring. The banks used as samples from this study are BRIS and BRI by looking at monthly publication reports on the BI website. From this research it is expected to provide information to the management and need in the banking industry. With this additional information, it is expected to be taken more accurately and can increase the level of expenditure from banks. This is very necessary considering the banking industry has a high level of expenditure. The high level of risk makes banking industry players continue to use methods to anticipate future risks. Expected after this research. Can be developed further.